SENYAWA BIOAKTIF RIMPANG JAHE (Zingiber officinale Roscue ) MENINGKATKAN RESPON SITOLITIK SEL NK TERHADAP SEL KANKER DARAH K-562 IN VITRO [Ginger Root Bioactive Compounds Increased Cytolitic Response of Natural Killer (NK) Cells Against Leucemic Cell L - Tejasari .; Fransiska Rungkat Zakaria (Jurnal Teknologi dan Industri Pangan, 2006)
Natural killer (NK) cell, a kind of lymphocyte cells, plays an important role in attacking infectious, immature, and cancer cell. Its function could be modulated by food bioactive compounds. This experiment was conducted to investigate the effects of ginger root bioactive compounds such as oleoresin, gingerol, and shogaol on cytolitic response of NK cell in vitro. Lymphocyte cells were isolated by centrifugation on ficoll-hypaque density (1,77 ?0,001 g/ml) method. Leukemic cells line K-562 as target cells(TC) labelled by [3H]-timidin, together with lymphocyte as effector cell (EC) were cultured in two ratio levels of EC : TC equal to 1:50 and 1:100), and two culture conditions, for 4 hours, respectively. Paraquate dichloride (1,1-dimethyl-4,4-bipyridilium dichloride) 3 mM was used to induce stress oxidative circumstance. Cytolytic capacity of NK cells was determined by percentage of TC lysed by NK cells, in normal and oxidative stress conditions. Statistical analysis showed that the effects of ginger bioactive compounds on cytolytic response of NK cell depended on the culture conditions, as shown by cultures in the presence of oleoresin, and gingerol, but not shogaol. In the lymphocyte culture without stress oxidative, oleoresin, gingerol and shogaol compounds increased significantly cytolytic response of NK cells cultured at a ratio of TC : EC equal to 1:50, with the highest increament of 65 % at oleoresin concentration of 50 ?g/ml. However, in culture at a ratio of TC : EC equals to 1:100, only oleoresin at a concentration of 50 ?g/ml increased significantly cytolytic response of NK cells with the highest increament of 8 %. Shogaol did not affect significantly NK cells cytolytic response. Under stress oxidative conditions, shogaol increased significantly cytolytic response of NK cells cultured at a ratio of TC:EC equal to 1:50, but the highest increament of 56 % , was by oleoresin at concentration of 50 ?g/ml. Meanwhile, oleoresin and gingerol did not increased significantly cytolytic response of NK cells. At a culture- ratio of TC: EC equal to 1:100, gingerol increased significantly cytolytic response of NK cells of 21 % at a concentration of 50 ?g/ml. However, oleoresin did not increased significantly cytolytic response of NK cells. In contrast, shogaol decreased significantly cytolytic response of NK cell with the highest decreament of 16 % at 200 ?g/ml. These findings verified that ginger root bioactive compounds increased cytolityc response of NK cells in destroying cancer cells, at certain conditions and concentrations, especially at low concentrations. Key words : ginger bioactive compound, oleoresin, gingerol, shogaol, stress oxidative, effector cell, target cell, natural killer cell, cytolytic response